Amylosporus guaraniticus sp. nov. (Wrightoporiaceae, Russulales) a new neotropical species from Paraguay - Campi Gaona, Michelle Geraldine (2017)
Amylosporus guaraniticus is described as a new species from Paraguay based on morphological characters and molecular evidence based on ITS and LSU markers. The species is characterized by its annual, pileate basidiomata, poroid hymenophore, a dimitic hyphal system with simple septate and double to multiple clamped generative hyphae and asperulated, amyloid basidiospores (4-6.5 × 3-4.5 μm). An identification key to Amylosporus species is presented.